Literature Review: Impact of Family Psychoeducation on the ability of families in caring the family members with schizophrenia - Cempaka, Anindya Arum (JURNAL NERS LENTERA, 2020)
Introduction: Family psychoeducation have emerged as a strongly supported evidence based practice in the treatment of schizophrenia. Family psychoeducation is designed to engage, inform, and educate family members, so that they can assist the person with schizophrenia in managing their illness. Method: This study aims to review the literature about implementation of family psychoeducation on the ability of families in caring the family members with schizophreni. Article search conducted electronically in some database : Sage, Sience Direct, Proquest, and Google Scholar, by January 2010 until August 2020. The keywords used were “Family psychoeducation”, “Schizophrenia”, “Family capability”, “Caring”, “Indonesia”. Results: Result showed in seven studies that Family psychoeducation effectively in improving the ability of family in treating people with schizophrenia. Conclusion: Family psychoeducation effectively in improving the ability of family in treating people with schizophrenia. Keywords: Family psychoeducation, Schizophrenia, Family capability, Caring, Indonesia.